Density and Functional Role of Zooplankton in The Coastal Waters of Bahu and Meras, North Sulawesi - Ali, Sitti Nur Haliszah; Koneri, Roni; Papu, Adelfia (JURNAL BIOS LOGOS, 2026)
The city of Manado is surrounded by waters with a long coastline. Most of the coastline is used for human activities. These activities include tourist attractions, ports, and trade centres. The sustainability of these sectors is highly dependent on the health of the marine ecosystem. One organism that plays an important role in the aquatic ecosystem is zooplankton. This study aims to calculate the density of zooplankton and analyse its functional role. The method used was exploratory descriptive, which is a research pattern that describes in detail or comprehensively the condition or status of zooplankton phenomena. This study was conducted at Bahu Beach and Meras Beach, North Sulawesi. The density value at Bahu Beach is 307.35 ind/m3 and at Meras Beach is 222.4 ind/m3. Zooplankton identified from two sampling points belonged to the phyla Arthropoda, Foraminifera, Annelida, Mollusca, and Cilliophora. The total number of genera found was 22. There were 1,032 consumer I individuals, 798 consumer II individuals, and 193 consumer III individuals.